Rancang Bangun Sistem Monitoring Kinerja Karyawan dan Penggajian Karyawan Konveksi berbasis web : Studi Kasus: FPN Collections - Alawiyah, Dini; Cahyana, Rinda (Institut Teknologi Garut, 2025)
Employee performance is a crucial factor in a company's success, especially in the convection industry which relies on labor productivity. Therefore, an effective performance monitoring and payroll system is indispensable to ensure fairness of compensation and improve employee motivation and productivity. Payroll in a convection company includes not only basic salary, but also bonuses, overtime, and deductions, which require transparent and accurate management.This research aims to develop a web-based system that integrates performance monitoring and employee payroll in a convection company. The method used is prototyping with five stages: communication, quick plan, modeling quick design, construction of prototype, and deployment delivery & feedback. Data Flow Diagram (DFD) is used for system design, while testing is done using the black box testing method.The results showed that this system can improve efficiency in performance monitoring and payroll management. The test resulted in a success rate of 87.6%, which is categorized as very good.